Implementasi Pembelajaran Make A Match Untuk Meningkatkan Kemampuan Siswa Kelas X TK SMKN 2 BATU - Azizah, Nur (J-PAI: Jurnal Pendidikan Agama Islam, 2020)
Abstract. Understanding Quranic materials in vocational students includes understanding how to read, the meanings, and the contents. Q.S. At-Taubah (10): 122 is one of the Quranic materials taught to students of class X SMK (vocational school). Most of the 10th-grade students at SMKN (State Vocational high School) 2 Batu in learning Surah Al-Taubah are only limited to reading comprehension with lacking in understanding the meaning and content. This condition occurs due to the lack of teachers in implementing various learning models that are varied and innovative. This research is a type of Classroom Action Research (CAR) with the aim to improve students' ability to understand Quranic material in surah At Taubah. The procedure for carrying out this research consists of two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The results showed that by using the "Make A Match" model, student learning outcomes in the application of the law of reading nun/tanwin and mim sukun in reading the Qur'anic letters showed an increase. It is proven by the increase in the average results of daily tests and classical completeness values. The average value of the class increased from 66.8 to 76.5 in the first cycle and increased to 82 in the second cycle. The percentage of classical completeness before taking action by 54% increased to 75% in the first cycle and increased to 96% in the second cycle.Keywords: Make a Match; Undertanding; Learning.